Comparative study on efficacy of traditional lysol based floor cleaners versus newer biological and sodium hypochlorite based floor cleaner in our institution - Shanmugam, Subbiah; ., Rajkiran (International Journal Of Community Medicine And Public Health, 2019)
Background: Floor disinfection plays a major role in patient to patient transmission of infections in hospital environment. In our hospital, lysol based floor cleaner was routinely used for floor cleaning. In our study we compare alternative methods of disinfection using sodium hypochlorite (NaOCl) based floor cleaner and biological (cows urine based) floor cleaner with traditional Lysol based floor cleaner. Methods: Three floor cleaners were used in the study (Lysol, NaOCl, biological cleaner). Study was conducted in our institution between August 2018 to October 2018. These floor cleaners were used in different floors and swab was taken every month to determine their efficacy of disinfection. Results: After initial culture of all three floor cleaner samples, the Lysol solution was culture positive for clostridium tetani spore. In first month, Lysol was used in both floor 1 and floor 2. In second month, NaOCl floor cleaner in floor 2 and biological cleaner in floor 1 was used. In third month, NaOCl floor cleaner for floor 1 and biological cleaner for floor 2 was used. Swabs taken at the end of each month was negative for culture except clostridium tetani spores were grown in floor 2 in corridor floor in which biological cleaner was used in third month. Conclusions: Floor cleaning with alternative reagents like NaOCl and biological cleaners are non inferior in disinfection of hospital environment in comparison with traditional lysol floor cleaner.